A survey on hepatitis B vaccination policies in genitourinary medicine in UK and Ireland. Issue 4 (August 1995) - el-Dalil, A; Radcliffe, K W; Bailey, J; Richmond, R A; Wade, A A
Abstract : OBJECTIVE--To determine the policies applied in genitourinary medicine (GUM) departments in the United Kingdom (UK) and Ireland with regard to hepatitis B vaccination. DESIGN--All genitourinary medicine consultants were sent a questionnaire requesting information concerning their selection criteria and the management of patients offered Hepatitis B vaccine. If no response was obtained a second questionnaire was sent. The survey was carried out in 1993. SETTING--All genitourinary medicine departments in UK and Ireland. PARTICIPANTS--234 consultants were sent the questionnaire. 153 consultants responded. RESULTS--Overall, there was a 65.4% response rate to the questionnaire. Almost all genitourinary physicians would offer the vaccine to male homosexuals and up to 74% offer it to all male homosexuals, intravenous drug users (IVDU) and prostitutes. Of the genitourinary physicians, 96% agreed that hepatitis B virus (HBV) serological markers should be checked prior to or simultaneously with vaccination, yet there was no agreement as to which marker should be performed. Up to 79% of consultants recalled the patients to check their response to vaccination but only 61% offered long term follow up after vaccination. CONCLUSION--HBV vaccine is offered to all male homosexuals, IVDU and prostitutes in GUM departments. Currently, the vaccine is not generally offered to patients who present with sexually transmitted diseases. Almost all genitourinary physicians (96%) agree that HBV serological markers should be checked prior to or simultaneously with the start of the vaccination course and 80% would request hepatitis B surface antibody levels after vaccination to identify inadequate responders and non-responders. From this survey, there appears to be a need for uniform post-vaccination HBV screening and timing and frequency of booster doses.